A three-Phase shunt active power filter with unified constant frequency integration control with RLC connection circuit - Ahmed, R.A.; Mekhilef, Saad; Ping, H.W. (2009)
This paper discusses a Modular Structure Multilevel Inverter (MSMI) with a Unified Constant Frequency Integration Control (UPC) which is used as an Active Power Filter (APF). APF is connected in shunt to the power system in order to sense the non-sinusoidal current drawn by the non-linear load and inject current to the transmission line which compensates the harmonics drawn by the load. This in turn helps having a power factor value close to one at the source side since the source current is forced to follow the source and thus be in phase with it. An APF topology is simulated for different connection parameters and its performance for each case is studied. Finally the results are compared to show that the topology proposed in this paper has a better harmonic reduction.